The role of sanctions and incentives in improving tax enforcement: A comparative study of developing countries - Putri, Devira Kusuma; Arum, Lingga Sekar; Duha, Nickyta Arcindy; Raisyah, Harfakhriz; Junior, Fransiskus; Wijaya, Suparna (Educoretax, 2024)
Tax enforcement is an important aspect of governance, and the use of sanctions and incentives plays an important role in shaping taxpayer compliance behavior. This research investigates the role of sanctions and incentives in enhancing tax enforcement in developing countries through a comprehensive literature study. By comparing strategies from advanced economies, analyzing factors influencing the effectiveness of sanctions and incentives, and exploring policy implications, the study provides valuable insights to optimize tax enforcement mechanisms. Findings highlight the importance of balancing sanctions and incentives, key factors influencing compliance behavior, and policy implications for enhancing tax enforcement in developing countries.